2017
DOI: 10.5858/arpa.2017-0031-oa
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Improving Utilization of Laboratory Testing

Abstract: Context.-The incorporation of best practice guidelines into one's institution is a challenging goal of utilization management, and the successful adoption of such guidelines depends on institutional context. Laboratorians who have access to key clinical data are well positioned to understand existing local practices and promote more appropriate laboratory testing.Objective.-To apply a novel approach to utilization management by reviewing international clinical guidelines and current institutional practices to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We investigated the characteristics of the family study cohort, and as expected, HH cases had median serum ferritin and transferrin saturation levels above the reference levels used for HH diagnosis 23,24 . Commonly accepted reference ranges for females are 200 ng/mL, and 45%, for serum ferritin and transferrin saturation, respectively, and for males are 300 ng/mL, and 50%, for serum ferritin and transferrin saturation, respectively.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We investigated the characteristics of the family study cohort, and as expected, HH cases had median serum ferritin and transferrin saturation levels above the reference levels used for HH diagnosis 23,24 . Commonly accepted reference ranges for females are 200 ng/mL, and 45%, for serum ferritin and transferrin saturation, respectively, and for males are 300 ng/mL, and 50%, for serum ferritin and transferrin saturation, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that 80 to 85% of HH cases are HFE C282Y homozygous 1 . Furthermore, serum ferritin concentration and transferrin saturation are common first line diagnostic markers for HH 23,24 . These results demonstrate the validity of the feature ranking approach.…”
Section: Discussionmentioning
confidence: 99%
“…DSAs have helped optimize testing in a number of clinical settings. [4][5][6] The goal of our study was to demonstrate that use of DSA-supported test ordering after pathologist evaluation decreases unnecessary overordering and omitted testing.…”
Section: Introductionmentioning
confidence: 99%